2018
DOI: 10.1152/physiolgenomics.00053.2018
|View full text |Cite
|
Sign up to set email alerts
|

R213G polymorphism in SOD3 protects against bleomycin-induced inflammation and attenuates induction of proinflammatory pathways

Abstract: Extracellular superoxide dismutase (EC-SOD), one of three mammalian SOD isoforms, is the sole extracellular enzymatic defense against superoxide. A known human single nucleotide polymorphism (SNP) in the matrix-binding domain of EC-SOD characterized by an arginine-to-glycine substitution at position 213 (R213G) redistributes EC-SOD from the matrix into extracellular fluids. We previously reported that knock-in mice harboring the human R213G SNP (R213G mice) exhibited enhanced resolution of inflammation with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Consistent with this notion is the finding that EcSOD R213G polymorphism is associated with reduced risk of COPD for smokers, but not for non-smoker (57,115). Gaurav were suppressed in EcSOD R213G mice (37) . Similar findings were observed for models of allergic airway inflammation (38,47).…”
Section: Copdmentioning
confidence: 63%
“…Consistent with this notion is the finding that EcSOD R213G polymorphism is associated with reduced risk of COPD for smokers, but not for non-smoker (57,115). Gaurav were suppressed in EcSOD R213G mice (37) . Similar findings were observed for models of allergic airway inflammation (38,47).…”
Section: Copdmentioning
confidence: 63%
“…Using NGS approaches, genetic studies on pulmonary fibrosis have made great progress, most of which have led to the discovery of mutations in genes related to telomere homeostasis [59]. Whole-lung transcriptome profiling showed dysregulated canonical pathways in the fibrosis mouse model, including the pathways for bacteria/virus recognition, inflammation, leukocyte extravasation, and ROS production [60]. By using scRNA-seq, Peyser et al [61] found that early events in lung fibrosis might not involve significant changes in fibroblast number, while the numbers of macrophages, dendritic cells (DCs), and proliferating myeloid cells are increased.…”
Section: Introductionmentioning
confidence: 99%
“…All mouse work was approved by the University of Colorado-Anschutz Medical Campus Institutional Animal Care and Use Committee. The lung tissue used in this study was obtained from the same cohort of mice used in our recently published study that analyzed mRNA sequencing data to enable direct comparison between the miR and mRNA sequencing analysis (14). As published, mice received standard chow and water ad libitum and were housed in the vivarium with a 14:10 h light-dark schedule.…”
Section: Methodsmentioning
confidence: 99%
“…Mice with a knock-in R213G EC-SOD SNP have reduced bleomycin-induced pulmonary fibrosis and enhanced resolution of inflammation relative to wild-type (WT) mice (35). Previous studies found disparate transcriptomic profiles between WT and R213G mice responsible for differential inflammation and immune function (14). However, it is unclear whether epigenetic regulation contributes to the differential expression of these immune and inflammatory genes.…”
Section: Introductionmentioning
confidence: 99%